1993
DOI: 10.1111/j.1432-1033.1993.tb18267.x
|View full text |Cite
|
Sign up to set email alerts
|

Biotin biosynthesis in higher plant cells

Abstract: Biotin biosynthesis was investigated in lavender cell cultures (Lavandula vera L.). Two different biological assays and two different HPLC procedures were used to identify all the intermediates involved in biotin biosynthesis. The pathway for biotin biosynthesis could be analyzed starting with [3H]pimelic acid as precursor, leading to labelled biotin and even to labelled biotinylated enzymes. Intermediates known from the bacterial pathway (7‐oxo‐8‐amino‐pelargonic acid, 7,8‐diamino‐pelargonic acid, dethiobioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 32 publications
(17 reference statements)
2
58
0
Order By: Relevance
“…Similar results were obtained with B. sphaericus [24]. Further evidence supporting 9-mercaptodethiobiotin as an intermediate comes from experiments in which the label from [$%S]mercaptodethiobiotin was incorporated into biotin by a cell-free system from B. sphaericus [26], and the isolation of a reaction intermediate from plant cells that was proposed to be 9-mercaptodethiobiotin [27].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar results were obtained with B. sphaericus [24]. Further evidence supporting 9-mercaptodethiobiotin as an intermediate comes from experiments in which the label from [$%S]mercaptodethiobiotin was incorporated into biotin by a cell-free system from B. sphaericus [26], and the isolation of a reaction intermediate from plant cells that was proposed to be 9-mercaptodethiobiotin [27].…”
Section: Introductionsupporting
confidence: 67%
“…Many groups have tried to identify a reaction intermediate for biotin synthase, which would help to elucidate the reaction mechanism [24,25,27,35,36]. Our observation of an intermediate was made possible only by the use of the biotin synthase assay that we developed with ["%C]dethiobiotin as substrate.…”
Section: Implications and A Working Model For The Biotin Synthase Reamentioning
confidence: 99%
“…Recently, Baldet et al reported that the conversion of dethiobiotin to biotin may proceed in two distinct steps involving 9-mercaptodethiobiotin as an intermediate in higher plant cells [30]. This intermediate may also be involved in biotin biosynthesis in bacteria including E. coli [31-331.…”
Section: Discussionmentioning
confidence: 99%
“…5). The Bio2 enzyme is considered to be a rate-limiting enzyme in the biotin synthesis pathway (21). Because biotin-dependent carboxylases are involved in various processes such as energy metabolism, gluconeogenesis, and fatty acid synthesis in plants, it is believed that the need for biotin increases in light conditions rather than in dark conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This step includes reactions that form a thiophene ring via the addition of a sulfur atom and is considered to be a rate-limiting step for biotin synthesis (21). In Arabidopsis, the expression of bio2 is reportedly regulated in response to development, light, the circadian period, and biotin starvation (16).…”
Section: Expression Of the Bio2 Gene In Pea Sprouts Is Suppressed Undmentioning
confidence: 99%